A case report of pancreatic metastasis from synovial sarcoma successfully treated by metastasectomy with adjuvant chemotherapy. Issue 39 (September 2016) - Makino, Yuki; Shigekawa, Minoru; Kegasawa, Tadashi; Suda, Takahiro; Yoshioka, Teppei; Iwahashi, Kiyoshi; Ikezawa, Kenji; Sakamori, Ryotaro; Yakushijin, Takayuki; Kajihara, Jun; Tomimaru, Yoshito; Eguchi, Hidetoshi; et al.
Abstract: Introduction: Synovial sarcoma is a malignant soft tissue sarcoma which arises near joints. The most frequent metastasis sites of synovial sarcoma are the lungs, lymph nodes, and bone. Pancreatic metastasis is quite rare; only 3 cases have been reported worldwide to date. We herein present the 4th case of pancreatic metastasis from synovial sarcoma. Methods and Results: A 32-year-old man underwent extended excision of synovial sarcoma in the left pelvis and femur in 2009. In 2013, follow-up contrast-enhanced computed tomography revealed a 35-mm heterogeneously enhanced mass in the pancreas body. Endoscopic ultrasound-guided fine needle aspiration of the mass revealed a diffuse proliferation of atypical spindle cells in a fascicular arrangement. Because the histology was quite similar to the resected specimen of synovial sarcoma in 2009, the mass was suspected to be a metastasis from synovial sarcoma. Laparoscopic distal pancreatectomy with adjuvant adriamycin/ifosfamide chemotherapy was subsequently performed. Synovial sarcoma-specific SS18-SSX1 (synovial sarcoma translocation, chromosome 18-synovial sarcoma X1) or SS18-SSX2 chimera mRNA was detected in the resected specimen, confirming the diagnosis of metastasis from synovial sarcoma. The patient did well for 30 months without recurrence. Conclusion: This case suggests that pancreatic metastasis from synovial sarcoma can be successfully treated by metastasectomy with adjuvant chemotherapy.